Relationship of adolescents’ internet and smartphone addiction with loneliness, sleep quality and academic achievement levels - Coşkun, Sabahat; Saray Kılıç, Hülya (Journal of Dependence, 2022)
Objective: The aim of this study is to determine the relationship between adolescents’ internet and smartphone addiction and their loneliness, sleep quality and academic achievement levels. Methods: This cross-sectional study was conducted between May 2019 and June 2019. A total of 407 students studying at a high school participated in the research. In the collection of data; Sociodemographic characteristics, “Internet Addiction Scale”, “Smartphone Addiction Scale”, “Sleep Quality Scale” and “UCLA Loneliness Scale” were used. Results: The mean age of the adolescents was determined as 16.72±1.34. According to the results obtained; Adolescents with internet addiction and limited internet addiction have worse sleep quality, higher levels of loneliness, lower academic achievement than those who do not show symptoms and the difference between them was found to be statistically significant. In addition, it was determined that as the level of smartphone addiction increased, poor sleep quality loneliness increased, while academic achievement scores decreased, and the relationship was found to be significant. Conclusion: It has been observed that the internet and smartphone addiction levels of adolescents negatively affect their sleep quality, loneliness and academic achievement. It is of great importance to identify these behavioral addictions at an early stage and to protect adolescents from the negative effects of addiction. For this reason, it is thought that training programs for the effective, safe and correct use of the internet and smart phones should be developed and disseminated for adolescents.